2008
DOI: 10.1093/annonc/mdn372
|View full text |Cite
|
Sign up to set email alerts
|

HPV in oral squamous cell carcinoma vs head and neck squamous cell carcinoma biopsies: a meta-analysis (1988–2007)

Abstract: These findings support the assumption that a correct distinction of HNSCC by site, together with the use of more sensitive HPV DNA detection methods, should be considered as essential prerogatives in designing future investigations into viral prevalence in head and neck tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
270
4
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(305 citation statements)
references
References 79 publications
22
270
4
9
Order By: Relevance
“…A high prevalence of HPV in oral cancers from India has been reported previously, suggesting that viral agents could cause additional mutations in the carcinogenic process, together with dietary habits and probably, in the presence of a given genetic predisposition (Balaram et al, 1995). A meta-analysis by Termine et al showed that overall prevalence of HPV DNA in oral SCC was 38.1% (Termine et al, 2008). With regards to the detection method, PCRbased studies reported a higher prevalence rate than ISH-based rates (39.9% versus 32.9%).…”
Section: Discussionmentioning
confidence: 86%
“…A high prevalence of HPV in oral cancers from India has been reported previously, suggesting that viral agents could cause additional mutations in the carcinogenic process, together with dietary habits and probably, in the presence of a given genetic predisposition (Balaram et al, 1995). A meta-analysis by Termine et al showed that overall prevalence of HPV DNA in oral SCC was 38.1% (Termine et al, 2008). With regards to the detection method, PCRbased studies reported a higher prevalence rate than ISH-based rates (39.9% versus 32.9%).…”
Section: Discussionmentioning
confidence: 86%
“…Our Li-Li Gan et al previous study with 44 patients showed that the incidence of HPV infection in OSCC in Wuhan was 40.4% (Zhao et al, 2009). This discrepancy might attribute to the different anatomic locations of tumors and techniques used to detect HPV-DNA (Termine et al, 2008). But the epidemiology studies including our previous study in Chinese population were almost limited by small samples, which cannot precisely reflect the real situation of HPV infection in China.…”
Section: Introductionmentioning
confidence: 82%
“…The discrepancy of different HPV prevalence found in OSCC in different studies might attribute to different anatomic locations of tumors, different sample origins (such as formalin-fixed, fresh biopsies, or oral exfoliated cells), different techniques used to detect HPV existence (such as PCR, P16 immunohistochemistry and in situ hybridization) (Termine et al, 2008) and different population involved in epidemiology studies. For example, the epidemiology in USA is about 38% infection in OSCC, whereas the meta-analysis of Chinese population indicated the prevalence in China is 47.47% (Termine et al, 2008;Zhu et al, 2012).…”
Section: Li-li Gan Et Almentioning
confidence: 98%
See 2 more Smart Citations